2015
DOI: 10.1158/1535-7163.mct-14-0492
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA ANRIL Promotes Non–Small Cell Lung Cancer Cell Proliferation and Inhibits Apoptosis by Silencing KLF2 and P21 Expression

Abstract: Recent evidence highlights long noncoding RNAs (lncRNA) as crucial regulators of cancer biology that contribute to essential cancer cell functions such as cell proliferation, apoptosis, and metastasis. In non-small cell lung cancer (NSCLC), several lncRNAs' expressions are misregulated and have been nominated as critical actors in NSCLC tumorigenesis. LncRNA ANRIL was first found to be required for the PRC2 recruitment to and silencing of p15 INK4B , the expression of which is induced by the ATM-E2F1 signaling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
294
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(309 citation statements)
references
References 38 publications
(32 reference statements)
15
294
0
Order By: Relevance
“…For example, knockdown of the lncRNA TATDN1 has been shown to inhibit tumor growth and metastasis in NSCLC cells by inhibiting β-catenin and Ezrin; thus, TATDN1 may be a potential prognostic factor and therapeutic target for NSCLC [21] . In addition, the lncRNA ANRIL has been found to be significantly upregulated in NSCLC tissues, and its expression promotes cell proliferation and inhibits cell apoptosis in vitro and in vivo [22] . Moreover, HOTAIR, MALAT1 and SBF2-AS1 have been shown to exert oncogenic functions in NSCLC [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, knockdown of the lncRNA TATDN1 has been shown to inhibit tumor growth and metastasis in NSCLC cells by inhibiting β-catenin and Ezrin; thus, TATDN1 may be a potential prognostic factor and therapeutic target for NSCLC [21] . In addition, the lncRNA ANRIL has been found to be significantly upregulated in NSCLC tissues, and its expression promotes cell proliferation and inhibits cell apoptosis in vitro and in vivo [22] . Moreover, HOTAIR, MALAT1 and SBF2-AS1 have been shown to exert oncogenic functions in NSCLC [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been reported to be important in cell apoptosis, particularly in the escape of cancer cells from apoptosis (20)(21)(22). To determine the impact of TRIM52-AS1 on RCC cell apoptosis, flow cytometry was performed to detect the rate of apoptosis in the cells.…”
Section: Downregulation Of Trim52-as1 Promotes Rcc Cell Apoptosis In mentioning
confidence: 99%
“…As CDKN1A is a tumor suppressor, we hypothesize that epigenetic changes, such as promoter methylation, may be one of the mechanisms underlying the low CDKN1A expression in RGA tissues; promoter methylation is capable of inhibiting gene transcript and protein expression, as identified by Watanabe et al (32), who suggested that abnormal genomic methylation may be involved in the reduced expression of CDKN1A in adult T-cell leukemia/lymphoma (32). A study conducted by Nie et al (33) indicated that long noncoding RNAs (lncRNA) may also serve a role in regulation of CDKN1A transcription; the authors demonstrated that the lncRNA antisense noncoding RNA in the INK4 locus was upregulated in non-small cell lung cancer (NSCLC) tissues, and that this lncRNA promoted NSCLC cell proliferation and inhibited NSCLC cell apoptosis through the inhibition of Krüppel-like factor 2 and CDKN1A transcription (33). These studies additionally demonstrate that CDKN1A is a key regulator of the cell cycle, and may be a target for cancer treatment.…”
Section: Discussionmentioning
confidence: 90%